The Impact of Cash Conversion Cycle (CCC) Towards Profitability of All Firms Listed on Indonesia Stock Exchange (IDX) in The Period of 2009-2019 (The Indonesian Journal of Business Administration, 2021)
Indonesia is one of the largest economies in the world, with a total population of around 269 million people, Indonesia economy accounts for the 10th largest in the world in terms of purchasing power parity. However, In the period of 2009 through 2019, the firms listed in Indonesia Stock Exchange (IDX) have experienced a fluctuating value in their profitability with the tendency to decline. Several researchers have found that profitability is influenced by working capital management. Working capital itself is a measure of a firm’s liquidity that available for businesses to operate which the components are including inventory, account receivables, and account payables. Tools to measure working capital is cash conversion cycle (CCC) which is considering the key aspect of current asset management. The objective of this research is to find evidence that cash conversion cycle (CCC) including its components Average Age Inventory (AAI), Average Collection Period (ACP), and Average Payment Period (APP) could impact the profitability of the firms listed on Indonesia Stock Exchange (IDX) in the period of 2009 through 2019. The data that is used in this research is covering 341 companies that are listed in the period of 2009 through 2019. The data analysis is conducted using fixed effect panel data regression. The findings of this research show that cash conversion cycle (CCC) and its components such as average age of inventory (AAI), average collection period (ACP), and average payment period (ACP) have an inversely significant impact towards profitability. Based on the findings it shows that the profitability of firms listed in Indonesia Stock Exchange is affected by cash conversion cycle.Keywords: Working Capital, Cash Conversion Cycle (CCC), Profitability